PERBANDINGAN METODE DEDUKTIF DENGAN INDUKTIF TERHADAP HASIL BELAJAR MATEMATIKA DITINJAU DARI MOTIVASI BELAJAR SISWA - Samsul Bahri; Andi Ika Prasasti Abrar; Andi Dian Angriani (Department of Mathematics Education Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2017)
Abstrak:Penelitian ini bertujuan untuk mengetahui gambaran hasil belajar matematika yang menggunakan metode deduktif dan induktif, gambaran hasil belajar matematika yang menggunakan metode deduktif dan induktif, perbedaan yang signifikan antara metode deduktif dengan induktif terhadap hasil belajar matematika ditinjau dari motivasi belajar siswa. Jenis penelitian ini adalah penelitian quasi eksperiment. Populasi dalam penelitian ini ialah seluruh siswa kelas XII IPS MAN Wajo terdiri dari 4 kelas, yang berjumlah 86 siswa. Penentuan sampel dengan cara random. Instrumen yang digunakan pada penelitian ini adalah tes hasil belajar dan angket motivasi belajar matematika. Teknik analisis yang digunakan adalah statistik deskriptif dan analisis statistik inferensial dengan uji F ANAVA dengan interaksi. Berdasarkan hasil analisis statistika deskriptif, diperoleh nilai rata-rata hasil belajar siswa menggunakan metode deduktif adalah 74,91 dan metode induktif adalah 88,95, nilai rata-rata motivasi belajar matematika siswa menggunakan metode deduktif adalah 65,73 dan metode induktif adalah 68,23. Berdasarkan analisis inferensial, diperoleh F0 > F tabel (3,911 > 3,24) dan nilai Sig. < = 0,021 < 0,05, maka Ho ditolak, artinya terdapat perbedaan yang signifikan antara metode deduktif dengan metode induktif terhadap hasil belajar matematika ditinjau dari motivasi belajar siswa kelas XII IPS MAN Wajo.Abstract:This study aims to find out the learning outcome in mathematics using Inductive Method, outcome in mathematics using Deductive Method, the description of students’ learning motivation using Inductive Method, the students' learning motivation using Deductive Method, to know the significant difference between Inductive Method and Deductive Method on the learning outcome in mathematics based on the learning motivation of students in social sciences major of grade 12 of Islamic Senior High School Wajo, Wajo regency. This research is a quasi-experimental design. The population was all the students of social sciences in grade 12 of Islamic Senior High school Wajo which consisted of 86 students. The sampling technique was simple random sampling. Instruments used were the learning outcomes test, questionnaire on learning motivation of mathematics and observation sheet. The techniques of analysis used were descriptive statistics and inferential statistical analysis with F test of ANAVA with interaction. Based on the results of data analysis using descriptive statistics for student's learning outcome using Deductive Method, the average score of this group was 74.91. On the other hand, the students’ learning outcome using Inductive Method reached the average score of 88.95. Theaverage score of students’ learning motivation in mathematics using deductive method was 65.73. As for students’ learning motivation using Deductive Method, the average score was 68.23. The result of ANAVA for hypothesis I is that F0 > F table, thus Ho is rejected. Therefore, it is concluded that there is a significant difference between Inductive Method and Deductive Method on Mathematics Learning outcome. As for the hypothesis II, the result obtained shows that F0 > F table, thus Ho rejected, then it is concluded that there are differences between students who have high motivation, moderate motivation and low motivation in their learning outcomes in mathematics. For the hypothesis III, it is revealed that F0> F table (3.911> 3.24) and the Sig value < α = 0.021 <0.05, hence Ho is rejected, where it indicates that there is a significant difference between Inductive Method and Deductive Method towards the learning outcome in mathematics based on the learning motivation of students in social sciences major of grade 12 of Islamic Senior High School Wajo, Wajo regency.